O princípio da inerência do risco na atividade empresarial - Paula, Luiz Gonzaga Modesto de (2019)
Every human activity has a potential for risk. Simple walking may result in stumbling. A baby sleeping in his crib may eventually hit his head on the railing and suffer an injury. In all activities, people surround themselves with care to avoid the worst. The father and mother, aware of the risks, pad the bars to avoid an accident. The risk exists to a greater extent in business activity, and most of the time the authorities do not adequately protect this exercise. When someone invests in a business activity, it creates a mechanism of economic activity in which it brings together its investors, encourages its suppliers, satisfies its consumers, creates jobs that will support the families of the workers, and generates taxes for the state. But you must be aware of the risks surrounding this activity. Risk in business is failure. The failure of the company affects the whole community where it is inserted because it frustrates all expectations and generates damages for the whole community that has united around the business activity. It is then up to the whole society to generate means and actions to eliminate as much as possible the risks of the company. They must recognize the existence, in the legal field, of the principle of inherent risk in business activity and collaborate, each in its sphere, to reduce these risks. From the legislator creating laws of protection, the interpreter in the adequacy of studies to the business reality, and the judge using these lenses in the solution of business difficulties. Based on a vision of human relations, among which the company excels, inserting this activity in a three-phase view of Law: legislation, interpretation and judgment, to finally examine the existing legislation on the operational difficulties of the company, and conclude by the need to review the infamous character of bankruptcy and the recovery of companies in crisis. This is the scope of this paper. Knowing the risks that surround it, we ask for early excuses if we do not reach the goal